Social determinants of access to minimally invasive hysterectomy: reevaluating the relationship between race and route of hysterectomy for benign disease - Price, Joan T.; Zimmerman, Lilli D.; Koelper, Nathan C.; Sammel, Mary D.; Lee, Sonya; Butts, Samantha F. (American journal of obstetrics and gynecology, 2017)
Racial and socioeconomic disparities exist in access to medical and surgical care. Studies of national databases have demonstrated disparities in route of hysterectomy for benign indications, but have not been able to adjust for patient-level factors that affect surgical decision-making. We sought to determine whether access to minimally invasive hysterectomy for benign indications is differential according to race independent of the effects of relevant subject-level confounding factors. The secondary study objective was to determine the association between socioeconomic status and ethnicity and access to minimally invasive hysterectomy. A cross-sectional study evaluated factors associated with minimally invasive hysterectomies performed for fibroids and/or abnormal uterine bleeding from 2010 through 2013 at 3 hospitals within an academic university health system in Philadelphia, PA. Univariate tests of association and multivariable logistic regression identified factors significantly associated with minimally invasive hysterectomy compared to the odds of treatment with the referent approach of abdominal hysterectomy. Of 1746 hysterectomies evaluated meeting study inclusion criteria, 861 (49%) were performed abdominally, 248 (14%) vaginally, 310 (18%) laparoscopically, and 327 (19%) with robot assistance. In univariate analysis, African American race (odds ratio, 0.80; 95% confidence interval, 0.65–0.97) and Hispanic ethnicity (odds ratio, 0.63; 95% confidence interval, 0.39–1.00) were associated with lower odds of any minimally invasive hysterectomy relative to abdominal hysterectomy. In analyses adjusted for age, body mass index, income quartile, obstetrical and surgical history, uterine weight, and additional confounding factors, African American race was no longer a risk factor for reduced minimally invasive hysterectomy (odds ratio, 0.82; 95% confidence interval, 0.61–1.10), while Hispanic ethnicity (odds ratio, 0.45; 95% confidence interval, 0.27–0.76) and Medicaid enrollment (odds ratio, 0.59; 95% confidence interval, 0.38–0.90) were associated with significantly lower odds of treatment with any minimally invasive hysterectomy. In adjusted analyses, African American women had nearly half the odds of receiving robot-assisted hysterectomy compared to whites (adjusted odds ratio, 0.57; 95%, confidence interval 0.39–0.82), while no differences were noted with other hysterectomy routes. Medicaid enrollment (compared to private insurance; odds ratio, 0.51; 95% confidence interval, 0.28–0.94) and lowest income quartile (compared to highest income quartile; odds ratio, 0.57; 95% confidence interval, 0.38–0.85) were also associated with diminished odds of robot-assisted hysterectomy. When accounting for the effect of numerous pertinent demographic and clinical factors, the odds of undergoing minimally invasive hysterectomy were diminished in women of Hispanic ethnicity and in those enrolled in Medicaid but were not discrepant along racial lines. However, both racial and socioeconomic disparities were observed with respect to access to robot-assisted hysterectomy despite the availability of robotic assistance in all hospitals treating the study population. Strategies to ensure equal access to all minimally invasive routes for all women should be explored to align delivery of care with the evidence supporting the broad implementation of these procedures as safe, cost-effective, and highly acceptable to patients.